Burnout Knowledge of Female Nurses during the COVID-19 Pandemic: Study at dr. Agoesdjam Hospital in Ketapang Regency, Indonesia - Arkanudin Arkanudin; Rupita Rupita (Randwick International of Social Science Journal, 2021)
The COVID-19 pandemic has hit Indonesia where the worrying situation has affected almost every all-region in Indonesia, including West Kalimantan. One of the referral hospitals for the case of COVID-19 in West Kalimantan is RSUD dr. Agoesdjam is the only one referral hospital in the Ketapang Regency area. This makes a critical situation, considering that Ketapang Regency is very large and there is only one referral hospital. The problem that arises later is the number of patients from various regions who come to check themselves at RSUD dr. Agoesdjam Ketapang, where this hospital has a limited number of doctors and health workers. This causes job burnout for health workers, where they have to work extra in monitoring and handling patients regularly in their work environment. This study uses a descriptive qualitative approach with an exploration of primary and secondary data. Primary data refers to the interview results while secondary data comes from journal searches and online media coverage. Based on the results and discussion in this study, it can be concluded that the COVID-19 situation in RSUD dr. Agoesdjam is quite worrying so that it increases the alertness of the hospital, in this case, the job burnout of health workers is increasing. The duties and responsibilities of nurses are a priority in handling COVID-19 patients and this case raises fear, worry, and energy burden and thoughts for health workers, especially nurses at RSUD dr. Agoesdjam Ketapang. Furthermore, the job burnout experienced by nurses in dealing with the COVID-19 situation is work overload, poor performance, fatigue, and reduced alertness because they are overshadowed by anxiety and worry.